‘Originality’ Revisited: Balancing Tradition and Agility in JLSC - Deborah Barreau (Journal of Librarianship and Scholarly Communication, 2013)
The basic structure and function of scholarly journals have remained largely unchanged since 1665, when the concepts of publisher, editor, and peer reviewer were outlined in the initial description of Philosophical Transactions (Zuckerman & Morton, 1971). The traditions that have developed since that time have become almost sacrosanct—journals that diverge from the three pillars of original submissions, blind peer review, and editorial authority (along with the slightly less inviolable fourth pillar of paper) are often viewed as lesser by scholars and the committees that evaluate them for promotion or tenure.